Sistem Informasi Point of Sales Berbasis Web di Perusahaan Bangunan Andalas Jaya - Chrislie, Enrico; Birowo, Sigit (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Andalas Jaya building company is engaged in the sale of building goods or materials and transactions carried out every day are quite large, in their activities of course they require an accurate information system to make it easier to make sales transactions and record stock of goods. Making this sales and purchase information system using the Visual Studio Code program and for the database using MySQL. Researchers consider that operational activities at the Andalas Jaya Building Company are still carried out manually. Therefore, the researcher will design a Point of Sales website system to help Andalas Jaya Building Company by conducting qualitative research to get conclusions from the required sales website system. In realizing the creation of a good Point of Sales system website, researchers took the first steps such as making a system design consisting of architectural design, use case diagrams, activity diagrams, entity relationship diagrams, interface designs, website menu structures, and system implementation. With the creation of a Point of Sales website at the Andalas Jaya Building Company, it is hoped that it can help the business transaction process become more effective and efficient for further researchers to add different features.